Ipsilateral axillary recurrence after breast conservative surgery: The protective effect of whole breast radiotherapy. Issue 1 (January 2017) - Gentilini, Oreste; Botteri, Edoardo; Leonardi, Maria Cristina; Rotmensz, Nicole; Vila, Jose; Peradze, Nickolas; Thomazini, Maria Virginia; Jereczek, Barbara Alicja; Galimberti, Viviana; Luini, Alberto; Veronesi, Paolo; Orecchia, Roberto
Abstract: Background and purpose: Whole breast radiotherapy (WBRT) is one of the possible reasons for the low rate of axillary recurrence after breast-conserving surgery (BCS). Patients and methods: We retrospectively collected data from 4, 129 consecutive patients with breast cancer ⩽2 cm and negative sentinel lymph node who underwent BCS between 1997 and 2007. We compared the risk of axillary lymph node recurrence between patients treated by WBRT ( n  = 2939) and patients who received partial breast irradiation (PBI; n  = 1, 190) performed by a single dose of electron intraoperative radiotherapy. Results: Median tumour diameter was 1.1 cm in both WBRT and PBI. Women who received WBRT were significantly younger and expressed significantly more multifocality, extensive in situ component, negative oestrogen receptor status and HER2 over-expression than women who received PBI. After a median follow-up of 8.3 years, 37 and 28 axillary recurrences were observed in the WBRT and PBI arm, respectively, corresponding to a 10-year cumulative incidence of 1.3% and 4.0% ( P  < 0.001). Multivariate analysis resulted in a hazard ratio of 0.30 (95% CI 0.17–0.51) in favour of WBRT. Conclusions: In this large series of women with T1 breast cancer and negative sentinel lymph node treated by BCS, WBRT lowered the risk of axillary recurrence by two thirds as compared to PBI.